The Moderating Effect of Consumer-Based Brand Equity towards The Effect of Social Media Content Marketing on Creating Consumer Engagement in The Case of Go-Jek - Timothy Rubino; Calvin Young (iBuss Management, 2019)
The unprecedented amount of social media usage urges marketers to find innovative ideas in promoting a brand, the company behind it and its products in social media. Currently, marketers are trying to engage their target consumer by creating creative marketing content. Go-Jek as a brand is subject to this research due to their active pursuit of content strategy and relatively high engagement. However, a recent study concluded a negative relationship between consumer engagement rate and content marketing usage. It is believed that consumer-based brand equity can help in enhancing a brand’s marketing program effectiveness. Therefore, this research would like to know whether consumer-based brand equity moderates the effect of social media content marketing in the creation of consumer engagement in the case of Go-Jek.This study will use simple random sampling and distribute questionnaire to people who have seen Go-Jek social media content marketing, have used the application, aged 17 above, and resides in three chosen cities. This study is analyzed using Moderated Regression Analysis. The findings show that social media content marketing influence the creation of consumer engagement. Furthermore, consumer-based brand equity was found to affect the relationship between social media content marketing in the creation of consumer engagement.  Keywords:Social media content marketing, consumer-based brand equity, consumer engagement